ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERGERAKAN INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA - Rama Masneri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This study aims to determine and analyze the influence of the Dow Jones index, the Hang Seng Index, the world oil price, interest rate of SBI and Inflation Stock Price Index (CSPI) on the Indonesia Stock Exchange (BEI). This study uses and analyzes the data in the period of 2005-2010 for each variable. The analysis used was multiple linear analysis and the research hypotheses was tested by using SPSS software version 17, which had previously tested for both normality of the data and classical assumptions on the data to qualify the regression equation.The results of this study shows that of the five independent variables in this study, there are only three variables that have a partially significant effect on the composite stock price index, namely Dow Jones index variable, the Hang Seng index, and the SBI interest rate. While the two other variables (oil prices and inflation) has no significant effect on IHSG, with various high capability for explanation (80%). This means that 80% of the JCI movement can be predicted from the movement of the five independent variables. Keywords: CSPI, Dow Jones Index, Hang Seng Index, World Oil Prices.